PANDANGAN IQBAL TENTANG MANUSIA - Sahjad M.Aksan (IAIN TERNATE, 2018)
The philosophy that underlies the overall structure of Iqbal's thought is the concept of Ego. For Iqbal; every thing in the universe has its own individuality, including matter even atoms have contained an ego colony in a low degree. and that's where an ego with a high degree (human) emerges. Individuality moves slowly uphill, climbing the ladder of existence to the point of development of perfection in humans.